Simão Mathias: encontro dos diversos, diálogo entre os vários - Oliveira, Daniel de (2009)
The present work refers to a study on Simão Mathias s contributions for the institutionalization of the science in Brazil. Its objective is to show how a professor Simão Mathias had fundamental importance for the development of institutionalization of the science in Brazil, by mentioning his biography, his books and its philosophies on the science and technology directed toward the scientific growth. The methodology used consists if collecting its contributions registered in books, magazines, testimonials of friends and scientists, and mainly in the publications of Simão Mathias